Relevansi Pemaknaan Hijrah pada QS: An-Nisa’ (4): 100: Studi atas Mufassir Abad Modern - Azis Fatkhurrohman, Abdul (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2024)
Hijrah as one of the phenomena recorded in the history of Islam during the time of the Prophet Muhammad Saw, is again associated by a number of Islamic preachers on social media. The conversation was prompted by the recent "humanitarian" tragedy between Israel and Palestine. At the same time, these preachers base their argument on QS an-Nisa' (4): 100 in addition to the historical context that is the background of the Prophet's hijrah. On this basis, this research aims to review the meaning of hijrah contained in QS an-Nisa' (4):100 through modern mufassirs. In this case, researchers try to place Tafsir al-Azhar and Tafsir al-Misbah as a representation of modern interpretation. Researchers used qualitative methods with content analysis of the two interpretations above. As a result, the two commentaries show an emphasis on the historical aspect of the hijrah carried out by the Prophet. On the other hand, both have different tendencies in seeing modern phenomena as a basis for historical significance to interpret the context of the Prophet's time. Hamka shows more assertiveness to "consider" the decision to hijrah which is interpreted by moving to a certain place or region, as the conditions experienced by the Prophet. In contrast to Quraish Shihab who plays a more descriptive role by not emphasizing the hijrah that occurred in the post-Nabian context.